Following the ESG principles as sustainable development factor of foreign economic activity of the Vladimir region - A. F. Baranova; O. S. Kulakova; D. D. Ignatov (Вестник университета, 2022)
The work is devoted to establishing a correlation between the effectiveness of foreign economic activity of the Russian region and the adherence of economic entities to the ESG principle. The international community recognizes that the most important goal today is the socio-economic development of territories while minimizing the negative anthropogenic impact on the environment. Today it is important that all types of economic activity are aimed at improving the quality of life. Therefore, there is an active development and popularization of business activity concepts aimed not only at achieving financial indicators, but also creating conditions for social justice, environmental safety and cleanliness of doing business. The paper analyses the importance of following the principles of sustainable development to maximize the effectiveness of foreign economic activity of Russian regions and attract foreign investment to certain territories of the country.